2017
DOI: 10.1039/c7ra11093f
|View full text |Cite
|
Sign up to set email alerts
|

Post-polymerization modification reactions of poly(glycidyl methacrylate)s

Abstract: Single and multiple post-polymerization modifications of poly(glycidyl methacrylate) scaffold through the nucleophilic ring-opening reactions of the pendent epoxide groups are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
114
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(117 citation statements)
references
References 105 publications
(133 reference statements)
2
114
0
1
Order By: Relevance
“…PGMA‐based copolymers are versatile precursors, useful in the preparation of a range of functional materials, underpinned by the ability of side‐chain epoxide rings to undergo ring‐opening reactions with a number of nucleophiles . The general synthetic strategy used in this study for the synthesis of PGMA‐based copolymers, followed by modification to yield the H 2 S delivery system, is summarized in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…PGMA‐based copolymers are versatile precursors, useful in the preparation of a range of functional materials, underpinned by the ability of side‐chain epoxide rings to undergo ring‐opening reactions with a number of nucleophiles . The general synthetic strategy used in this study for the synthesis of PGMA‐based copolymers, followed by modification to yield the H 2 S delivery system, is summarized in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…These pendant groups enable further modifications through various chemistries, including ring‐opening reactions with nucleophiles, and facilitating the robust attachment of films to surfaces . Polymerized GMA, poly(GMA), is known for biocompatibility and versatility as previous research has found utility for poly(GMA) and its copolymers in gene delivery, polymer scaffolds, and self‐healing materials . Poly(GMA) has additional uses in industrial and consumer settings including automotive coatings, protective finishes, adhesives, and electrical laminates.…”
Section: Introductionmentioning
confidence: 99%
“…8 Polymerized GMA, poly(GMA), is known for biocompatibility and versatility as previous research has found utility for poly(GMA) and its copolymers in gene delivery, polymer scaffolds, and self-healing materials. 9,10 Poly(GMA) has additional uses in industrial and consumer settings including automotive coatings, protective finishes, adhesives, and electrical laminates. While GMA and poly(GMA) have been well researched, GMA has no commercial complements with similar functionality, which could broaden and diversify the applications of epoxy-functional materials.…”
mentioning
confidence: 99%
“…Thus, there is a need to develop new polymeric materials as films. Glycidyl methacrylate (GMA) monomer, often used to produce functional polymers, is very reactive, cheap, and suitable for various polymerization reactions . Various secondary amines cause the ring‐opening reaction to the epoxy groups of GMA, which leads to the production of tertiary amine and hydroxy‐based bifunctional polymers .…”
Section: Introductionmentioning
confidence: 99%